Breaking Out of Fragility : A Country Economic Memorandum for Diversification and Growth in Iraq - World Bank (Washington, DC: World Bank, 2020)
Iraq is at a crossroads. Almost two decades after the 2003 war, the country remains caught in a fragility trap, facing increasing political instability, growing social unrest, and a deepening state-citizen divide. Amid a multitude of crises—including an oil price shock, the COVID-19 pandemic, and recent instability and protests—coupled with poor economic policies, a lack of reforms, and an inability to tackle corruption, Iraq is having its worst annual economic growth performance in 2020 since the fall of the Saddam regime. But with every crisis comes an opportunity to reform. Iraq can embark on a long but much-needed path toward structural transformation, one that could leave its economy less dependent on oil and more driven by private sector activity. Such a path can no longer be avoided, as has been illustrated by the widespread protests since October 2019. This report highlights what Iraq can do to sustain future growth; it also shows why Iraq has not yet managed to achieve high levels of diversified growth alongside peace, stability, and a better standard of living for its people. Iraq’s high levels of fragility and conflict--reinforced by high oil dependency--hinder the country’s prospects for economic reform and growth. Despite Iraq’s existing sociopolitical and economic environment, three encouraging messages emerge from this report. First, there is a peace dividend in Iraq. Iraq’s per capita GDP was about one-fifth lower in 2018 than it would have been if not for the conflict beginning in 2014. Thus, maintaining peace can by itself be a strong driver of growth. Second, Iraq has latent export potential for a variety of goods that, if tapped, could diversify the country’s economy, raise living standards, and boost economic resilience. Third, Iraqi agriculture could be revived to serve as a pillar of a more diversified and private sector–led economy.